Engineering practices on surface damage inspection and performance evaluation of concrete bridges in China. (2nd July 2021) - Chen, Airong; Fang, Xurui; Pan, Zichao; Wang, Dalei; Pan, Yue; Peng, Bo
Abstract·: This paper mainly demonstrates some experiences in China regarding surface damage inspection and performance evaluation of reinforced concrete (RC) bridges. To begin with, the mechanisms of the major damages of RC bridges such as chloride attack, concrete carbonation, and rebar corrosion are briefly reviewed. A statistical result of concrete cracking that exists in (prestressed) concrete bridges is presented as well. Second, the inspection practices of surface damages such as crack by using computer vision and deep learning on the RC pylons of the Jiang‐Yin Yangtze River bridge are demonstrated. Third, the specifications used in China for the performance evaluation of RC bridges are introduced. Its general philosophy and framework are explained. The Xia‐Men bridge is taken as an example to illustrate how to conduct a quantitative performance evaluation by following the instructions in China specifications. Finally, some perspectives on more advanced and efficient inspection techniques and performance evaluation methods are provided.